2004
DOI: 10.1289/ehp.6690
|View full text |Cite
|
Sign up to set email alerts
|

Developmental effects of chlorpyrifos extend beyond neurotoxicity: critical periods for immediate and delayed-onset effects on cardiac and hepatic cell signaling.

Abstract: The fetal and neonatal neurotoxicity of chlorpyrifos (CPF) and related insecticides is a major concern. Developmental effects of CPF involve mechanisms over and above cholinesterase inhibition, notably events in cell signaling that are shared by nonneural targets. In the present study, we evaluated the immediate and long-term effects of CPF exposure of rats during different developmental windows [gestational days (GD) 9-12 or 17-20, postnatal days (PN) 1-4 or 11-14] on the adenylyl cyclase (AC) signaling casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 75 publications
5
52
0
1
Order By: Relevance
“…In the Kingdom of Saudi Arabia (KSA), chlorpyrifos (CPF) (O, O'-diethyl3, 5, 6-trichloro-2-pyridinyl-phosphoro-thioate), a broadspectrum organo-phosphorous (OP) insecticide, has been widely used for the control of agricultural pests [2]. It has been reported that OP compounds are highly toxic to vertebrates [3] and CPF is particularly considered to be neurotoxic [4], cardiotoxic, hepatotoxic [5] and immunotoxic [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the Kingdom of Saudi Arabia (KSA), chlorpyrifos (CPF) (O, O'-diethyl3, 5, 6-trichloro-2-pyridinyl-phosphoro-thioate), a broadspectrum organo-phosphorous (OP) insecticide, has been widely used for the control of agricultural pests [2]. It has been reported that OP compounds are highly toxic to vertebrates [3] and CPF is particularly considered to be neurotoxic [4], cardiotoxic, hepatotoxic [5] and immunotoxic [6].…”
Section: Introductionmentioning
confidence: 99%
“…This period of susceptibility also extends into the neonatal period in experimental animals . For instance, Meyer et al (2004) studied the immediate and long-term effects of exposure of neonatal rats to the organophosphate pesticide chlorpyrifos on gestation days 9-12 and 17-20 or postnatal days 1-4 and 11-14. Cardiac responses were measured by pharmacological challenge of adenylyl cyclase activity with forskolin, isoproteronol, and glucagons.…”
Section: Consequences Of Exposuresmentioning
confidence: 99%
“…Producto de esto y de las investigaciones que informaban sobre los problemas de salud, se creó en Estados Unidos, en 1965, la Agencia para la Protección del Medio Ambiente (EPA), encargada desde entonces de evaluar los beneficios y peligros de los plaguicidas, siendo sus investigaciones un referente en los demás países del mundo sobre su eficacia y efectos(3). ción muscular, cambios en la frecuencia cardíaca y broncoespasmo, progresando a convulsiones y coma (1,4,(12)(13)(14)(15)(16).…”
Section: El Problema Histórico De Los Plaguicidasunclassified